2021
DOI: 10.1029/2020wr027404
|View full text |Cite
|
Sign up to set email alerts
|

A Changing Hydrological Regime: Trends in Magnitude and Timing of Glacier Ice Melt and Glacier Runoff in a High Latitude Coastal Watershed

Abstract: Discharge from western drainages of Juneau Icefield is increasing and has yet to pass 'peak water' as glaciers lose mass• Annual glacier ice melt volumes have increased by 10% per decade, glacier runoff by 3%, and total runoff by 1.4%• Peak glacier ice melt volumes are increasing and arriving earlier, with impacts for downstream ecosystem function

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 116 publications
(299 reference statements)
1
6
0
Order By: Relevance
“…as observed in Alaska (Hugonnet et al, 2021;Young et al, 2021). Poleward expansions were comparable between the three types of vegetation, with rates up to 20.8 km decade −1 .…”
Section: Biomesupporting
confidence: 58%
“…as observed in Alaska (Hugonnet et al, 2021;Young et al, 2021). Poleward expansions were comparable between the three types of vegetation, with rates up to 20.8 km decade −1 .…”
Section: Biomesupporting
confidence: 58%
“…Generally, the specific discharge in heavily glacierized watersheds was greater than those of non‐glacierized watersheds, which is consistent with other temperate glacierized watersheds (e.g., Fleming, 2005). Based on regional glacier mass balance studies and modeling, most of the glaciers within the KB and LC region are losing mass leading to increased freshwater yields to coastal environments (Deb et al., 2015; Larsen et al., 2015; Neal et al., 2010; Radić et al., 2014; Valentin et al., 2018; Yang et al., 2020; Young et al., 2021). As glaciers recede different runoff regimes will emerge altering the timing of freshwater inputs.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, within Southeast Alaska stream discharge has yet to reach peak water from glacier melt (Young et al., 2021). As watersheds lose glacial ice they evolve and develop vegetative cover and soils and increase storage of organic carbon (Buma & Barrett, 2015; Chandler, 1943).…”
Section: Introductionmentioning
confidence: 99%
“…This supports previous research across a similar gradient in glacier coverage (0%–48%) that suggested the impact of glacier‐derived sediment on POC bio burial should peak at intermediate catchment glacierization since sediment production and export decrease with lower glacier coverage but the production of POC bio increases as soil carbon stocks develop following glacier loss (Hood et al., 2020). Since glacial loss decreases summertime runoff over the long term (O'Neel et al., 2015; Young et al., 2021), future glacier shrinkage in the coastal mountain watersheds that ring the Gulf of Alaska may eventually lower POC bio concentration and export (a function of concentration and discharge) to coastal waters during the main glacial runoff season.…”
Section: Resultsmentioning
confidence: 99%